Data and planting density on the production and quality seed the triticale (X Triticosecale Wittmack). - Mendoza-Elos, Mariano (2011)
Theobjective of this study was to evaluate the effects of sowingdates and seeding rates on triticale seed yield and quality.This work was performed during the autumn-winter seasonin 2006-2007, at the research station of The TechnologicalInstitute of Roque, located at km 8 of the highway Celaya-Juventino Rosas, Celaya, Guanajuato, Mexico. We used threecultivars of triticale of different genetic origin (Roque I, AN-31 and AN-105) with one formula per hectare of 120-100-100, NPK. Three sowing dates were evaluated, November9, November 23, and December 7, and fi ve seeding ratesat each planting date, 50 kg/ha, 75 kg/ha, 100 kg/ha, 125kg/ha and 150 kg/ha. The variables evaluated were plantheight, ear length, seed yield, vigor, and germination. Theexperimental design was a randomized complete blockdesign with a factorial arrangement. The optimal sowingdate for seed production was November 9, resulting in ayield of 5,305 t/ha. This treatment resulted in the highestvalues for ear length, plant height, vigor, and germination.When selecting important traits to produce high quality seed,through sowing density, the highest plant population wasobtained with 125 kg/ha resulting in a yield of 3,834 t/ha,vigor of 82.0% and germination of 89.83%.